Juvenile competency adjudication in California criminal court: a defense attorney’s participation and observation of a criminal competency trial - Hanley, Michael W. (Working paper)
The present work is oriented to readers unfamiliar with the American criminal justice system. Legal issues are examined vis-à-vis an empirical case study of a juvenile defendant tried in adult criminal court due to curious elements of American law. The issue litigated before a 12-member jury was not the substantive merits of guilt or innocence of the alleged criminal conduct, but whether the particular juvenile defendant was “competent” to stand trial in adult court. The work sets out the basic substantive and procedural rules of competency litigation in California state court and the extent to which these rules are shaped by federal constitutional mandates. The work then presents the evidence and controversies that transpired in the course of the competency litigation.